People, food and biodiversity: The making of inclusive, nutritious school meals. A visual Narrative - Shijagurumayum, Meghajit Sharma; Estrada Carmona, Natalia; Elias, Marlene; Jones, Sarah; Zaremba, Haley; Krishnan, Smitha (2025)
Developed through a participatory validation process in India, this visual narrative brings together community knowledge and practitioner experience to reflect on how school meal programmes connect food, nutrition, agrobiodiversity, and inclusion. It is designed to support shared understanding, dialogue, and learning across different actors engaged in school meal systems.